TRACING THE ROOTS OF EMOTIONAL INTELLIGENCE: A CRITICAL REVIEW OF FOUNDATIONAL THEORIES AND MODELS - Singh, Rajbir; Shweta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Emotional intelligence (EI) has appeared as a critical domain in understanding human behavior, interpersonal dynamics, and cognitive-affective functioning. Emotional intelligence is the ability to achieve self-defined goals by combining intrapersonal and interpersonal skills. Analyzing and controlling own and other people's sentiments while effectively using them to achieve objectives is part of emotional intelligence (EI). Individuals possess a high EI may sustain strong interpersonal relationships and are capable of understanding the emotive requirements of others. Accomplishment in life is largely dependent on one's Emotional Intelligence. The ability model, mixed model, and Bar-On model are a few of the Emotional Intelligence theoretical frameworks that are examined in this work along with their historical context. Various dimensions and elements are discussed of each model. Descriptive research design is being employed in this study. By integrating theoretical perspectives on developmental pathways, the goal of the research is to give a thorough grasp of how emotional intelligence develops and can be developed.